CGMP-Elevating Compounds and Ischemic Conditioning Provide Cardioprotection Against Ischemia and Reperfusion Injury via Cardiomyocyte-Specific BK Channels. Issue 24 (12th December 2017) - Frankenreiter, Sandra; Bednarczyk, Piotr; Kniess, Angelina; Bork, Nadja I.; Straubinger, Julia; Koprowski, Piotr; Wrzosek, Antoni; Mohr, Eva; Logan, Angela; Murphy, Michael P.; Gawaz, Meinrad; Krieg, Thomas; et al.
Abstract : Background: The nitric oxide–sensitive guanylyl cyclase/cGMP-dependent protein kinase type I signaling pathway can afford protection against the ischemia/reperfusion injury that occurs during myocardial infarction. Reportedly, voltage and Ca 2+ -activated K + channels of the BK type are stimulated by cGMP/cGMP-dependent protein kinase type I, and recent ex vivo studies implicated that increased BK activity favors the survival of the myocardium at ischemia/reperfusion. It remains unclear, however, whether the molecular events downstream of cGMP involve BK channels present in cardiomyocytes or in other cardiac cell types. Methods: Gene-targeted mice with a cardiomyocyte- or smooth muscle cell–specific deletion of the BK (CMBK or SMBK knockouts) were subjected to the open-chest model of myocardial infarction. Infarct sizes of the conditional mutants were compared with litter-matched controls, global BK knockout, and wild-type mice. Cardiac damage was assessed after mechanical conditioning or pharmacological stimulation of the cGMP pathway and by using direct modulators of BK. Long-term outcome was studied with respect to heart functions and cardiac fibrosis in a chronic myocardial infarction model. Results: Global BK knockouts and CMBK knockouts, in contrast with SMBK knockouts, exhibited significantly larger infarct sizes compared with their respective controls. Ablation of CMBK resulted in higher serum levels of cardiac troponin I and elevated amounts of reactive oxygen species, lower phosphorylated extracellular receptor kinase and phosphorylated AKT levels and an increase in myocardial apoptosis. Moreover, CMBK was required to allow beneficial effects of both nitric oxide–sensitive guanylyl cyclase activation and inhibition of the cGMP-degrading phosphodiesterase-5, ischemic preconditioning, and postconditioning regimens. To this end, after 4 weeks of reperfusion, fibrotic tissue increased and myocardial strain echocardiography was significantly compromised in CMBK-deficient mice. Conclusions: Lack of CMBK channels renders the heart more susceptible to ischemia/reperfusion injury, whereas the pathological events elicited by ischemia/reperfusion do not involve BK in vascular smooth muscle cells. BK seems to permit the protective effects triggered by cinaciguat, riociguat, and different phosphodiesterase-5 inhibitors and beneficial actions of ischemic preconditioning and ischemic postconditioning by a mechanism stemming primarily from cardiomyocytes. This study establishes mitochondrial CMBK channels as a promising target for limiting acute cardiac damage and adverse long-term events that occur after myocardial infarction. Abstract : Supplemental Digital Content is available in the text.